MENERAPKAN KONSEP PENGAMBILAN KEPUTUSAN TAKTIS DALAM BERBAGAI SITUASI BISNIS: MEMBELI ATAU MEMPERTAHANKANKAN AKTIVA PADA PT MUTIARA SELATAN - Windriawati, Windriawati; Abdullah, Rudi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
The purpose of this research is to analyse the relevant cost in decision making to buy or maintain fixed assets at PT Mutiara Selatan. Qualitative descriptive research method. The results of the study when viewed from the analysis of relevant costs should replace the old fixed assets with new ones should apply anilisis relevant cost in making company decisions, especially in making decisions to buy or maintain fixed assets. Decision making always involves the future so that future data relevant to the decision of the data available. Information that exists in the company comes in different forms so that it is difficult to choose which one is most appropriate for a decision. To assist companies in making the right decision to choose the best alternative action among the available alternatives, cost calculations are needed using various cost methods. One of them is relevant cost.